Strategi Pengembangan dalam Upaya Meningkatkan Penjualan pada Distributor Bahan Bangunan CV.Maju Mapan Sejahtera - Puspita, Yunita Dwi; Arija, Haifa Hannum; Patmasari, Eka Kurnia (Universitas Pasundan, 2025)
The growth of the construction sector has increased the demand for building materials and intensified competition among building material distributors. This condition requires companies to implement appropriate business development strategies to remain competitive and improve sales performance. This study aims to identify the strategies applied in the business development of CV. Maju Mapan Sejahtera as a building material distributor in responding to the increasingly competitive business environment in Batang Regency. This research employed a qualitative method with a case study approach. Data were collected through in-depth interviews and documentation involving the business owner, employees, and retail partners of CV. Maju Mapan Sejahtera. The collected data were analyzed using descriptive qualitative analysis through the SWOT framework to examine internal and external factors affecting the company. The results indicate that the company’s main strengths include service quality, competitive pricing, strong business relationships, and a strategic business location. The identified weaknesses are limited product brand variety and the lack of promotional activities. Business opportunities are supported by the continuous growth of construction activities in the region, while the primary threats arise from intense competition and price sensitivity among retail partners. SWOT-based business development strategies are essential to enhance competitiveness and ensure business sustainability.